2021
DOI: 10.1158/1078-0432.ccr-21-0342
|View full text |Cite
|
Sign up to set email alerts
|

Darolutamide Potentiates the Antitumor Efficacy of a PSMA-targeted Thorium-227 Conjugate by a Dual Mode of Action in Prostate Cancer Models

Abstract: Most patients with prostate cancer undergoing antiandrogen treatment will develop resistance, and thus, novel effective treatments are needed. Here, we explore the combination of the antibody-based targeted alpha therapy PSMA-TTC and the androgen receptor inhibitor darolutamide in preclinical prostate cancer models. This combination is well-tolerated and exhibits synergistic antitumor efficacy. We demonstrate a dual mode-ofaction for this combination treatment, where androgen inhibition (1) induces PSMA expres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Our results demonstrate that these effects of topoisomerase-2 inhibition drive PSMA expression. This is in keeping with results from other groups reporting that BRCA2 CRISPR knockout and treatment with PSMA-TCC, an alpha particle emitting RLT toward PSMA, induce PSMA expression (24,25). Interestingly, our screen also identified that toposisomerase-1 inhibition and EGFR inhibition upregulate PSMA; as topoisomerase-1 inhibitors can also cause DNA single-and double-strand breaks this is perhaps not surprising (31).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results demonstrate that these effects of topoisomerase-2 inhibition drive PSMA expression. This is in keeping with results from other groups reporting that BRCA2 CRISPR knockout and treatment with PSMA-TCC, an alpha particle emitting RLT toward PSMA, induce PSMA expression (24,25). Interestingly, our screen also identified that toposisomerase-1 inhibition and EGFR inhibition upregulate PSMA; as topoisomerase-1 inhibitors can also cause DNA single-and double-strand breaks this is perhaps not surprising (31).…”
Section: Discussionsupporting
confidence: 91%
“…We have previously demonstrated that mCRPC with DNA damage repair (DDR) defects, including deleterious alterations in BRCA2 and ATM, have significantly higher PSMA expression (15). Interestingly, preliminary studies suggest that BRCA2 CRISPR knockout and alpha emitting radioisotopes that result in DNA damage may upregulate PSMA (24,25). Overall, we hypothesized that these data support a functional role for PSMA in nucleotide pool maintenance and that the expression of PSMA is dynamic, not static in prostate cancer cells, with DNA damage-inducing agents increasing PSMA expression.…”
Section: Introductionmentioning
confidence: 99%
“…The ARI darolutamide is approved for non-metastatic CRPC in key markets ( 78 , 79 ) and more recently for use in combination with docetaxel for metastatic hormone-sensitive prostate cancer in the United States ( 79 ). Darolutamide has been shown to induce PSMA expression in prostate cancer cell lines and xenografts ( 80 , 81 ), providing a rationale for combining the drug with a PSMA-TTC. In prostate cancer xenograft models, darolutamide-mediated increase of PSMA expression facilitated tumor uptake of PSMA-TTC, and darolutamide also impaired PSMA-TTC-mediated induction of DNA damage repair genes ( 80 ).…”
Section: Ttcs In Combination With Other Cancer Therapiesmentioning
confidence: 99%
“…Darolutamide has been shown to induce PSMA expression in prostate cancer cell lines and xenografts ( 80 , 81 ), providing a rationale for combining the drug with a PSMA-TTC. In prostate cancer xenograft models, darolutamide-mediated increase of PSMA expression facilitated tumor uptake of PSMA-TTC, and darolutamide also impaired PSMA-TTC-mediated induction of DNA damage repair genes ( 80 ). Furthermore, the combination of PSMA-TTC plus darolutamide demonstrated synergistic inhibition of tumor growth in xenograft models ( 80 ).…”
Section: Ttcs In Combination With Other Cancer Therapiesmentioning
confidence: 99%
See 1 more Smart Citation